2012
DOI: 10.1590/s1678-91992012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Bee venom treatment reduced C-reactive protein and improved follicle quality in a rat model of estradiol valerate-induced polycystic ovarian syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is a low grade inflammatory disease characterized by hyperandrogenemia and chronic anovulation. C-reactive protein (CRP), released by adipocytes, plays a key role in PCOS. Apis mellifera honeybee venom (HBV) contains a variety of biologically active components with various pharmaceutical properties. This study was designed to assess the possibility of HBV application as an anti-inflammatory therapeutic agent. To induce PCOS, 1 mg/100 g body weight estradiol valerate (EV) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The body weight of EV‐treated rats was comparable to that of control animals . However, the weight of inguinal fat depots was higher in the former than in the latter group.…”
Section: Estrogen‐induced Modelsmentioning
confidence: 75%
See 2 more Smart Citations
“…The body weight of EV‐treated rats was comparable to that of control animals . However, the weight of inguinal fat depots was higher in the former than in the latter group.…”
Section: Estrogen‐induced Modelsmentioning
confidence: 75%
“…The body weight of EV-treated rats was comparable to that of control animals. 60 However, the weight of inguinal fat depots was higher in the former than in the latter group. There was no difference in insulin sensitivity between treated and untreated rats.…”
Section: Metabolic Features and Adipositymentioning
confidence: 82%
See 1 more Smart Citation
“…In rats treated with HBV, the number of primordial and preantral follicles and corpora lutea increased, whereas the number of cysts decreased significantly compared to the sham group. In addition, some corpora lutea were observed in the HBV group, which was considered a sign of relative improvement in PCOS ovaries [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The direct and indirect roles of COX-2 (through TNF-alpha) in the thickening of the theca layer of the ovary have been reported [ 9 ]. We demonstrated that COX-2 was overexpressed in PCOS rats [ 10 ]. However, the role of COX-2 overexpression during mammalian ovary cycles is still less well defined.…”
Section: Introductionmentioning
confidence: 99%